About time : narrative, fiction and the philosophy of time - Currie, Mark, 1962- (Frontiers of theory., 2007)
About Time brings together ideas about time from narrative theory and philosophy. It argues that literary criticism and narratology have approached narrative primarily as a form of retrospect, and demonstrates through a series of arguments and readings that anticipation and other forms of projection into the future offer new analytical perspectives to narrative criticism and theory. The book offers an account of 'prolepsis' or 'flashforward' in the contemporary novel which retrieves it from the realm of experimentation and places it at the heart of a contemporary mode of being, both personal and collective, which experiences the present as the object of a future memory. With reference to some of the most important recent developments in the philosophy of time, it aims to define a set of questions about tense and temporal reference in narrative which make it possible to reconsider the function of stories in contemporary culture. It also reopens traditional questions about the difference between literature and philosophy in relation to knowledge of time. In the context of these questions, the book offers analyses of a range of contemporary fiction by writers such as Ali Smith, Ian McEwan, Martin Amis and Graham Swift.